Involvement of activator protein-1 family members in β-catenin and p300 association on the genome of PANC-1 cells. Issue 2 (February 2022) - Doi, Tomomitsu; Hojo, Hironori; Ohba, Shinsuke; Obayashi, Kunie; Endo, Motoyoshi; Ishizaki, Toshimasa; Katoh, Akira; Kouji, Hiroyuki
Abstract: Wnt/β-catenin is believed to regulate different sets of genes with different coactivators, cAMP response element-binding protein (CREB)-binding protein (CBP) or p300. However, the factors that determine which coactivators act on a particular promoter remain elusive. ICG-001 is a specific inhibitor for β-catenin/CBP but not for β-catenin/p300. By taking advantage of the action of ICG-001, we sought to investigate regulatory mechanisms underlying β-catenin coactivator usage in human pancreatic carcinoma PANC-1 cells through combinatorial analysis of chromatin immunoprecipitation-sequencing and RNA-sequencing. CBP and p300 preferentially bound to regions with the TCF motif alone and with both the TCF and AP-1 motifs, respectively. ICG-001 increased β-catenin binding to regions with both the TCF and AP-1 motifs, flanking the genes induced by ICG-001, concomitant with the increments of the p300 and AP-1 component c-JUN binding. Taken together, AP-1 possibly coordinates β-catenin coactivator usage in PANC-1 cells. These results would further our understanding of the canonical Wnt/β-catenin signaling divergence. Abstract : Wnt; β-catenin; Coactivator CREB-binding protein; p300; AP-1.